Association between parent-child sexual communication and the sexual intention among youth in Malaysia: Sex difference as a moderator - Sasha Silva, Erolis Silva; Tang, Jia Hang; Ong, Qian Xing (2021)
Throughout these few years, baby dumping cases in Malaysia had been arising and one of the causes of the issue was sexual debut at a young age. The consequences of premarital sex included unwanted pregnancy, child abandonment and an increase in sexual infection transmission. As parents or guardians were regarded as the gateway in children to receive sexual information, this study aimed to investigate the relationship between parent-child sexual communication (permissive and restrictive) and sexual intention among youth in Malaysia. Meanwhile, the sex of children will act as a moderator for the relationships. A total of 454 participants (57 percent females; 62.3 percent Chinese; Mage = 21.84, SDage = 1.92) were recruited through an online survey with the use of the purposive sampling method. The result showed both fathers and mothers tend to deliver more restrictive messages toward their youth children compare to permissive messages. The present study also indicated that the sex of children and sexual intercourse experience significantly predicted the sexual intention of youths in Malaysia but not the restrictive and permissive father-child sexual communication. Besides, there was no moderating effect of children’s sex on the relationship between (restrictive and permissive) parent-child sexual communication and sexual intention of youths in Malaysia. The present study has enriched literature regarding the sexual intention of youths in Malaysia. As this study found parent communication does not predict children’s sexual intention, authorities were recommended to pay more attention to Internet which is regarded as most received source for sexual information.